Prevalence of Physical Impairment Among the Elderlly Persons of the Tehran City in 1385 - Afsoon Nodehi Moghadam; Fatemeh Ehsani Fard (University of Social Welfare & Rehabilitation Sciences, 2007)
Objectives: Musculoskeletal pain is common in elderly people with prevalence range from 10% to 71%. Musculoskeletal pain is found to be a strong risk factor for disability in elderly woman. The purpose of this study is to examine the prevalence of physical impairment of elderly people. Methods & Materials: A physiotherapist has evaluated elderly persons files in four physiotherapy centers during 1384-85. Results: Knee osteoarthritis and low back pain respectively were the most common causes of physical impairment in elderly women. Prevalence of knee osteoarthritis is increasing. This increase is likely due to several factors: advancing age of population, increasing injuries and rapidly advancing rates of obesity. Age–related change of intervertebral disks, decreased back muscle strength and decreased bone mineral density may lead to low back pain. Conclusion: Knee osteoarthritis and low back pain are the most commom causes of physical impairment.